The quadratic formula is given by:
x = (-b ± √(b^2 - 4ac)) / (2a)
For the equation -2x^2 - 7x + 13 = 0, we have:
a = -2, b = -7, c = 13
x = (-(-7) ± √((-7)^2 - 4(-2)(13))) / (2(-2))
Simplifying further:
x = (7 ± √(49 + 104)) / (-4)
x = (7 ± √(153)) / (-4)
Therefore, the solutions to the quadratic equation -2x^2 - 7x + 13 = 0 are:
x = (7 + √(153)) / (-4)
x = (7 - √(153)) / (-4)
So the final answer is:
x = (7 + √(153)) / (-4), (7 - √(153)) / (-4)
Solve the following quadratic equation using the quadratic formula. −2x2−7x+13=0 **Note: Make sure to enter both solutions together in the space provided using the ± symbol. For example: x={12±10−−√} (If you need help with this, reach out to your teacher.) (1 point)
1 answer